Wave load on a navigation lock sliding gate. (15th April 2018) - Cavallaro, Luca; Iuppa, Claudio; Scandura, Pietro; Foti, Enrico
Abstract: The wave load on a navigation lock sliding gate equipped with a ballast tank is investigated assuming the linear wave theory is valid and using the eigenfunction expansion matching method to solve the governing equations. The correctness and the limits of the solution have been checked by comparing the results with those of a numerical code which solve the full non linear Navier-Stokes equations. The results relating to the effect of the geometrical parameters and wave characteristics on the load acting on the gate are presented and discussed. The ballast tank is found to increase the complexity of the phenomenon in relation to the wave interaction with the gate. The results indicate that the peak value of the vertical force occurs for wave numbers mostly dependent on the tank length and on the tank position along the depth, while the thickness has a smaller influence. The ballast tank has also a significant effect on the horizontal dynamic force acting on the gate, which vanishes when the wave number takes particular values. Finally, the moment applied to the gate shows a dependency on the geometrical and hydrodynamic parameters similar to that of the forces. Highlights: Wave load on a navigation lock gate equipped with a ballast tank has been studied. Linear wave theory and eigenfunction expansion method were adopted. Several diagrams are reported which show the relation between wave load and the parameters related to geometrical and wave characteristics.